Android, Bible. Aplikasi Alkitab Saat Teduh Pada Mobile Device Berbasis Android - D’laila Rumy, Krishella Naomi; Anom Cahyadi Putra, I Gusti Ngurah; Gede Suhartana, I Ketut (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
ABSTRACT Along with the development of technology, the use of mobile devices as a companion in carrying out daily activities has greatly facilitated mankind. This study aims to design an android-based Bible application, this application aims to make it easier for users to access the Bible on a smartphone device. In this Bible application, it consists of chapters that, when touched with a finger, will contain the entire contents of the chapter you want to read. This is because some phones already have more functions and capabilities than just basic functions. Android as an operating system that can be embedded on mobile devices has the ability to be able to install applications needed by application users. Seeing these considerations, the author wants to build an android-based mobile application. The expected results of this study are an android-based Bible application that applies language translation (TB), a language that is easier for users to understand. Keywords : Android, Bible.